TAMAN INTERAKTIF DI WADUK PLUIT SEBAGAI RUANG KEGIATAN PUBLIK BAGI MASYARAKAT DI JAKARTA - Maharani, Tiara; Hardiana, Ana; Mustaqimah, Ummul (ARSITEKTURA, 2015)
Designing Interactive Pluit Reservoir Park motivated by the needs unmet green space in the city of Jakarta. The existence of green space can be function as a public space by residents. Public space is a container that takes residents to interact socially in outer space. Pluit Reservoir ia a new green space that also has another function as a public space. Green open space in the middle of the urban environment helps to improve the climate and environment of the city. Design issues is the need for Jakarta residents of an ideal public space can not be fully met by local governments such as the activities housed, circulation, utilities, as well as physical and psycological comfort. Design method used is based on the theory of an ideal open space concept. Ideal open space concept obtained through environmental comfort, convenience visitor psychology, the need of relaxation, active activities, and passive activities within the park. These criteris are the basis for the design of Interactive at Pluit Reservoir Park. The result obtained are design Interactive park that can accommodate not only residents but also social needs, make room for plants to grow and thrive for the preservation and welfare of the citizens of Jakarta.Keyword :Â City Green Space, Interactive Park, Public space